2022
DOI: 10.1007/s12264-022-00985-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Roles of β-amyloid in Regulating Synaptic Function: Implications for AD Pathophysiology

Abstract: The physiological functions of endogenous amyloid-β (Aβ), which plays important role in the pathology of Alzheimer's disease (AD), have not been paid enough attention. Here, we review the multiple physiological effects of Aβ, particularly in regulating synaptic transmission, and the possible mechanisms, in order to decipher the real characters of Aβ under both physiological and pathological conditions. Some worthy studies have shown that the deprivation of endogenous Aβ gives rise to synaptic dysfunction and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 259 publications
0
14
0
Order By: Relevance
“…Research suggests that elevated Aβ damages synapses 1 , but it's crucial to highlight that most prior studies explore supraphysiological levels of exogenous Aβ, not physiological increases in endogenous Aβ. Indeed, evidence from mouse studies points to a hormetic effect of Aβ, where high levels of Aβ are synaptotoxic, but picomolar increases in Aβ often enhance synaptic function 3,[90][91][92][93][94][95][96] . Our observation that increased endogenous Aβ concentration in HBSCs increases the expression of synaptic transcripts, provides evidence that a similar hormetic role of Aβ may be present in human brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that elevated Aβ damages synapses 1 , but it's crucial to highlight that most prior studies explore supraphysiological levels of exogenous Aβ, not physiological increases in endogenous Aβ. Indeed, evidence from mouse studies points to a hormetic effect of Aβ, where high levels of Aβ are synaptotoxic, but picomolar increases in Aβ often enhance synaptic function 3,[90][91][92][93][94][95][96] . Our observation that increased endogenous Aβ concentration in HBSCs increases the expression of synaptic transcripts, provides evidence that a similar hormetic role of Aβ may be present in human brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotoxicity of the longer Aβ fragments and cell to cell seeding could also be mediated via a non-cell autonomous mechanism such as microglial activation [ 100 , 101 ]. It has been shown that reduced endogenous Aβ may also impair synaptic function [ 102 ]. Therefore, also the strongly diminished Aβ40 levels of APP Iberian could explain the negative effects of the Iberian mutation on synapse formation.…”
Section: Discussionmentioning
confidence: 99%
“…Full-length APP directly regulates metabolism in the CNS and peripheral tissue and can modulate mitochondrial functions [ 38 , 39 , 40 ]. It can be cleaved by proteases in different ways to produce a variety of short peptides, some of which, e.g., β-amyloid, possess toxic properties [ 40 , 41 ].…”
Section: Physiological Roles Of Amyloidogenic Ppsmentioning
confidence: 99%
“…Under physiological conditions, Aβ production is reportedly associated with neuronal activity [ 43 ] and regulated by the sleep/wake cycle [ 44 ]. A deficiency in endogenous Aβ causes synaptic dysfunction and cognitive defects, whereas a mild increase enhances long-term potentiation and leads to neuronal hyperexcitability [ 41 ].…”
Section: Physiological Roles Of Amyloidogenic Ppsmentioning
confidence: 99%